Pengaruh Orientasi Kewirausahaan, Orientasi Pasar, Lingkungan Eksternal Bisnis dan Kapasitas Penyerapan Terhadap Kinerja Bisnis - Indra Kurniawan (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2020)
The purpose of this study was to determine and explain whether entrepreneurial orientation, market orientation, external environment and performance delivery capacity had a significant effect on business performance, using this type of quantitative research with an explanatory research approach, with respondents in this study being actors/ owners / managers of SME sector decision makers. However, the results of this study indicate that Entrepreneurship Orientation has a significant effect on Business Performance, the Entrepreneurship Orientation variable has a significant effect on Market Orientation.The Entrepreneurial Orientation variable has a significant effect on Absorption Capacity, the Entrepreneurial Orientation variable has a significant effect on the External Business Environment, the Market Orientation variable has a significant effect on Performance, Variables Absorption Capacity, has no significant effect on Business Performance. Business External Environment Variables have a significant effect on Business Performance.